Is Drug-Related Violence Fueling Emigration from Central America? - Leonardo Bonilla-Mejía; Jessica Bracco; Andres Ham Gonzalez; Leonardo Pe\~naloza-Pacheco (Institute of Labor Economics (IZA), 2025)
We study how drug-related violence affects emigration from Central America, a region with rapidly rising migration to the United States. Using multiple data sources, we apply an instrumental variables strategy based on proximity to drug-trafficking routes and coca production in Colombia. We find that violence significantly increases intentions, plans, and preparations to emigrate–especially to the U.S.–with stronger effects among young and high-skilled individuals. Mediation analysis suggests this response is driven by declining economic activity and, more importantly, deteriorating labor market conditions caused by escalating violence.
Keywords: J61; O15; N96; 330; drug trafficking; violence; economic activity; labor markets; migration